LIBERAL TAIWAN VERSUS ILLIBERAL SOUTH KOREA: THE DIVERGENT PATHS OF ELECTION CAMPAIGN REGULATION. (November 2020) - You, Jong-sung; Lin, Jiun-Da
Abstract: South Korea and Taiwan have developed very different sets of election campaign regulations. While both countries had highly restrictive campaign rules during the authoritarian era, they have diverged since democratic transition. South Korea still imposes numerous restrictions on campaigning activities, but Taiwan has removed most of the restrictions. We explore the causes of these divergent trajectories through comparative historical process tracing, focusing on critical junctures and path dependence. We find that incumbency advantage and containment of new opposition parties were the primary objectives of introducing stringent regulations under the authoritarian regimes in both countries. The key difference was that, during the democratic transition, legislators affiliated with the opposition parties as well as the ruling party in South Korea enjoyed the incumbency advantage but that opposition forces in Taiwan did not. As a result, the opposition in Taiwan fought for liberalization of campaign regulations, but the South Korean opposition did not.